Learning Problems at Early Childhood Education in Kota Raja Sub-District, Kupang City During Coronavirus Disease Pandemic (Indonesian Journal of Early Childhood Education Studies, 2022)
Online learning is learning, using both a learning application and a social network. East Nusa Tenggara, especially Kupang city is one province that is also affected by the covid-19 outbreak. The learning process in the network in various schools, especially at the level of Early Childhood Education in Kota Raja sub-district, Kupang city found various problems among teachers, learners, and parents of students. The aims of the study are to 1) analyze the online learning process 2) and solutions to solve online problems in Early Childhood Education. This research was conducted at Early Childhood Education level in Kota Raja sub-district, Kupang city. The subjects used in this study were 19 early childhood education teachers and 19 students' parents in Kota Raja sub-district. This study uses a qualitative research type with a descriptive approach. Data collection techniques use interview techniques and questionnaires. Data analysis includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that online learning in the Covid-19 era is not going well; various problems are encountered in the field, both problems experienced by teachers, parents of students, and students. The problems include (1) time, (2) the limitations of the infrastructure, internet network, and understanding, (3) many assignments, (4) and students feeling bored. The problems found can be overcome by (1) involving teachers in various training, (2) seeking various sources and (3) parents providing more time for their children, (4) and providing motivation and support. Keywords: Problems of online learning; Early Childhood Education programs; Covid-19.